Depression, Burnout and Suicide in Physicians Insights from Oncology and Other Medical Professions - Grassi, Luigi; McFarland, Daniel; Riba, Michelle B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a reference and contextual basis for depression, burnout and suicide among oncology and other medical professionals. Oncology as a medical subspecialty is at a unique apex of this crisis. While the same pressures in medicine certainly apply to oncologists, oncology is particularly stressful as a changing field with diverse patient and societal expectations for outcomes. In addition to experiencing the stress of caring for patients that could succumb to their cancer diagnoses, these professionals are regularly confronted with an onslaught of new medical information and a landscape that is changing at a breakneck pace. These are just a few factors involved in the increasing rates of burnout among oncologists as well as other medcial professionals. By addressing a gap in identifying mental health problems among health care professionals, this book sheds light on mental health problems and suicide among physicians. Importantly, this book is a call to action of the professional and administrative organizations to work on improving mental health of physicians. Anxiety and depression affect not only the individual doctor but also patient care. Given the increasing attention to these issues along with limited yet applicable data regarding how to address these issues, the text aims to bring the latest data face to face with consensus opinion and can be used to ultimately enhance oncologic and psychiatric practices. Written by experts in the field, Depression, Burnout and Suicide in Physicians: Insights from Oncology and Other Medical Professions aims to significantly increase awareness and contribute to understanding the necessity of preventive measures on individual, family, and care givers levels.
The problem of Burnout, Depression, and Suicide in Physicians: A general overview -- Medical Professionalism and Physician Dignity: Are we at risk of losing it? -- Burnout in Medicine -- Depression and substance use disorders in physicians -- Suicide and suicide risk in physicians -- Screening and Assessment of Burnout With a Focus on Oncology Healthcare Providers -- The Ethical Implications of Burnout: A Moral Imperative to Prioritize Physician Well-Being, Resilience, and Professional Fulfillment -- Euthanasia and Medical Assistance in Dying as challenges for physicians well-being -- Moral Distress in Physicians -- Embitterment in the workplace -- Prevention of burnout through resilience, wellness programs, and civility in the work environment -- Cultivating Resilience and Preventing Burn Out: A Mindful Multi-Pronged Intervention Approach.
Keywords: Psychiatry; Oncology; Internal medicine; Psychiatry; Oncology; Internal Medicine; Depression -- psychology; Burnout, Professional -- psychology; Social Alienation -- psychology; Suicide -- psychology; Physicians -- psychology